ANALISIS BAHAYA PADA AKTIVITAS PEKERJAAN KETINGGIAN PEMASANGAN FIBER OPTIC DENGAN METODE JOB SAFETY ANALYSIS DI INDIHOME - Putra, Wandy Setiawan (Program Studi Kesehatan dan Keselamatan Kerja, 2020)
The research objective is to identify hazards and risks in the work process of installing fiber optic at a height at the Balikpapan branch of IndiHome PT Telkom. The research method used a qualitative approach, identification of hazards and risks using the JSA instrument. The results obtained in the work process of installing fiber optic in Indihome, there are 13 work steps that have been identified as many as 99 potential hazards with 36 risks. The work stages have a high risk, namely the risk of being hit by another vehicle at this stage (transportation of personnel, tools and materials) and the risk of falling from a height at that stage (climbing stairs, installing fiber optic cable connectors to ODP and descending stairs). The conclusion is that the fiber optic installation work consists of 13 work steps with 99 identified potential hazards and 36 possible risks